CFD study and experimental verification of steady flow in Bi-leaflet heart valve hinge - Wang, Junhong. (2008)
Since the first bi-leaflet mechanical heart valve (BMHV), St Jude Medical (SJM), was introduced for replacement of diseased natural heart valve in 1977, it has since remained the most popular valve. This is because it has a great advantage of hemodynamic performance than other prosthetic heart valves. BMHV's two semi-lunar leaflets, precisely pivoted by hinges, enable maximum effective orifice area and thus enhance performance hemodynamically. The hinge design of BMHV plays a critical role for proper valve functioning. Recent discoveries of an unacceptable thrombosis formation rate within the hinge pocket of the failed Medtronic Parallel™ (MP) BMHV indicated that the irrational organized hinge flow structure was a great hazard resulting in improper valve functioning. Hinge flow studies of MP, SJM and On-X® valves elucidated that the "positive-washing" effect in the hinge region was very crucial to wash-off potential stagnation flow. In this project, flow over a partially protruded hinge was investigated for "positive-washing" effect. This protruded hinge design takes the form of a partial sphere, exposing into the main flow stream. This hinge concept was developed at the Nanyang Technological University.